Effect of cycloplegia on corneal biometrics and refractive state - Bagheri, Abbas; Feizi, Mohadeseh; Shafii, Aliakbar; Faramarzi, Amir; Tavakoli, Mehdi; Yazdani, Shahin (Journal of ophthalmic & vision research, 2018)
Purpose: To determine changes in refractive state and corneal parameters after cycloplegia with cyclopentolate hydrochloride 1% using a dual Scheimpflug imaging system. Methods: In this prospective cross-sectional study patients aged 10 to 40 years who were referred for optometric evaluation enrolled and underwent autorefraction and corneal imaging with the Galilei dual Scheimpflug system before and 30 minutes after twice instillation of medication. Changes in refraction and astigmatism were investigated. Corneal biometrics including anterior and posterior corneal curvatures, total corneal power and corneal pachymetry were compared before and after cycloplegia. Results: Two hundred and twelve eyes of 106 subjects with mean age of 28 ± 5 years including 201 myopic and 11 hyperopic eyes were evaluated. Mean spherical equivalent refractive error before cycloplegia was -3.4 ± 2.6 D. A mean hyperopic shift of 0.4 ± 0.5 D occurred after cycloplegia (P < 0.001). The astigmatism power did not significantly change (P = 0.8), however, 26.8% of eyes with significant astigmatism experienced a change of more than 5 degrees in the axis of astigmatism. Changes in posterior corneal curvature were scant but statistically significant (P = 0.001). Moreover, corneal thickness was slightly increased in the central and paracentral regions (P < 0.001 and P < 0.001, respectively). Conclusion: Cycloplegia causes a hyperopic shift and astigmatism axis changes, along with an increase in central and paracentral corneal thickness and change in posterior corneal curvature. The effects of cycloplegia on refraction and corneal biometrics should be considered before cataract and refractive surgeries.